Ionospheric Scintillation During Night Time Beyond EIA, Using GPS - Chandel, Babita (International Journal of Scientific Research and Management (IJSRM), 2015)
Ionospheric scintillation is the rapid change in the phase and/or the amplitude of a radio signal as it passes through small scale plasma density irregularities in the ionosphere. These scintillations not only can reduce the accuracy of GPS receiver pseudo-range and carrier phase measurement but also can result in a complete loss of lock on a satellite. Scintillation in the ionosphere varies as the sun spot number (SSN), Geomagnetic index (o < Kp < 9), time of year, time of day, geographical position. Most scintillation occurs for a few hours after sunset during the peak years of the solar cycle. Typically delay locked loop/phase locked loop designs of GPS receivers enable them to handle moderate amount if scintillations. Consequently, any attempt to determine the effects of scintillations on GPS must consider both predictions of scintillation activity in the ionosphere and residual effect of this activity after processing by a receiver. In this work dual frequency (f1 = 1.5 GHz, f2 = 1.2 GHz) GPS data recorded at mid latitude station Palampur (Geographic latitude 32.117 0 N, longitude 76.5330 E) have been analyzed to monitor the amplitude scintillation index (S4) for April 2014. The analyzed data is used to study the ionospheric scintillation at mid latitude. It is found that at mid latitude there is the ionospheric scintillation in 28 days in pre night hours and one day in post night hours.